Growth and Seed Yield Response of Aeschynomene histrix to Cattle Manure and Plant Row Spacing in Southern Benin - Houndjo, Daniel; ADJOLOHOUN, SÉBASTIEN; Gbenou, B; SAIDOU, ALIOU; AHOTON, Léonard; HOUINATO, MARCEL ROMUALD BENJAMIN; SINSIN, AUGUSTIN BRICE (My University, 2019)
Scarcity of legume forage seeds in Benin contribute to their low adoption by farmers. The effects of animal manure/phosphorus fertilizer and row spacing on growth and seed yields of Aeschynomene histrix was studied (over a period of 3 years) in University of Abomey-Calavi (Benin). The experimental design was a split plot with 4 row spacing (20, 40, 60 and 80 cm) as the main plots and 6 sources of fertilizers (40 kg P2O5.ha-1, dry cattle manure rates of 0, 4, 8, 12, and 16 t.ha-1) as subplots. Onset of branching, plant height, onset of flowering, onset of podding, pod filling were assessed from selected plants on weekly basis starting from 4 WAS, seed yield and forage production at maturity. The results showed that an increase in cattle manure rates significantly (P<0.05) increased seed and forage yields of up to 307.48 kg ha-1 and 4.34 tons.ha-1, respectively. Over three years, plant spacing of 40 cm produced significantly (P<0.05) more seed than seed yield obtained from 20 cm, 60 cm and 80 cm. Regard to fertilizers, 12 tons cattle manure produced significantly more seed than seed yield through 0, 4, 8 and 16 tons.ha-1 cattle manure and 40 kg P2O5 kg.ha-1. Based on findings 12 t.ha-1 of cattle manure spread uniformly two weeks before sowing in rows 40 cm apart, should provide a satisfactory of A. histrix seed production in Southern Benin.
Keywords: Aeschynomene histrix; seed; forage; cattle manure; row spacing; phosphore; Benin